Translanguaging in English Language Teaching - Neupane, Padam Prasad (BMC Journal of Scientific Research, 2021)
This study explores teachers’ perspectives and practices on translanguaging in English language teaching. Especially, it focuses on how English language teachers perceive and explicate the meaning of translanguaging. The researcher got the primary data from the teachers in different private and public schools in Chitwan. All the respondents were studying in the 4th year of B.Ed major English at Birendra M. Campus Bharatpur; they all were teachers as well. First of all, some survey questions which were related to the study were sent to them via mail and got the written responses by the same means. It happened in such a way because of the lockdown due to the COVID-19. To understand the issue further, I arranged the interview and focus group discussion. I followed the standard process of analysis i.e., coding, categorizing, thematizing, and discussion. Respondents were aware of translanguaging and they took it positively. They agreed that bringing the native languages of every student to classrooms was challenging. They claimed that translanguaging enhances students’ creativity and participation in class.